Atmospheric evidence for a global secular increase in carbon isotopic discrimination of land photosynthesis - Keeling,RF; Graven,HD; Welp,LR; Resplandy,L; Bi,J; Piper,SC; Sun,Y; Bollenbacher,A; Meijer,HAJ (Proceedings of the National Academy of Sciences of the United States of America, 2017)
A decrease in the 13C/12C ratio of atmospheric CO2 has been documented by direct observations since 1978 and from ice core measurements since the industrial revolution. This decrease, known as the 13C-Suess effect, is driven primarily by the input of fossil fuel-derived CO2 but is also sensitive to land and ocean carbon cycling and uptake. Using updated records, we show that no plausible combination of sources and sinks of CO2 from fossil fuel, land, and oceans can explain the observed 13C-Suess effect unless an increase has occurred in the 13C/12C isotopic discrimination of land photosynthesis. A trend toward greater discrimination under higher CO2 levels is broadly consistent with tree ring studies over the past century, with field and chamber experiments, and with geological records of C3 plants at times of altered atmospheric CO2, but increasing discrimination has not previously been included in studies of long-term atmospheric 13C/12C measurements. We further show that the inferred discrimination increase of 0.014 ± 0.007‰ ppm−1 is largely explained by photorespiratory and mesophyll effects. This result implies that, at the global scale, land plants have regulated their stomatal conductance so as to allow the CO2 partial pressure within stomatal cavities and their intrinsic water use efficiency to increase in nearly constant proportion to the rise in atmospheric CO2 concentration.